2016
DOI: 10.1155/2016/5430708
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Thoracic Spontaneous Spinal Epidural Hematoma

Abstract: A 33-year-old male patient experienced temporary sensory loss and weakness in the right lower extremity one month prior to admission. The patient was admitted to a private clinic with a three-day history of acute onset of sensory loss and weakness in both lower extremities and was treated and followed up with a prediagnosis of transverse myelitis and the Guillain-Barre syndrome (GBS). The patient was subsequently transferred to our clinic and the neurologic examination revealed paraplegia in both lower extremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Secondly, the cervical epidural hematoma usually produces rapid deterioration. Beatty and Winston proposed arterial bleeding as the source in cervical epidural hematomas [1,3,4,17].…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the cervical epidural hematoma usually produces rapid deterioration. Beatty and Winston proposed arterial bleeding as the source in cervical epidural hematomas [1,3,4,17].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Although early surgery is recommended, there are reports of successful conservative treatment [1]. There is a trend towards hemilaminectomy and partial laminectomy also [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition of the symptoms and rapid diagnostic evaluation is essential to minimize delay in treatment of SSEH. Several studies have shown that MRI is the preferred diagnostic method of SSEH, [ 1 , 5 , 10 , 11 ] which may explain the increased report of the SSEH. Conventional MRI can estimate the bleeding occurrence, location, size, and severity of the spinal cord compression, based on the signal intensities of hematomas in T1 and T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by Blauby in 1808. [ 1 ] The incidence is estimated at 0.1 per 100,000 individuals. [ 2 , 3 ] The classical presentation of it includes an acute onset of severe, sometimes radiating back or neck pain, followed by signs and symptoms of rapidly evolving nerve root or spinal cord compression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation